PENETUAN FORMULA UNTUK MENETAPKAN ESTIMASI KOLESTEROL-LDL - Nugraha, Gilang; Edijanto, Soebagijoh Poegoeh (UNUSA Press, 2018)
Abstract: Measurement LDL-Cholesterol (LDL-C) can be performed by estimating LDL-C (cLDL-C) inthe blood. In addition to the first proposed Friedewald formula, several new formulas that promise betterexamination in determining LDL-C levels, proposed by Anandaraja, Puavilai, Chen, Vujovic, deCordova and Dansethakul. The subjects of the study were patients who performed routine lipid profileexamination in Institution of Clinical Pathology of Gedung Pusat Diagnostik Terpadu RSUD Dr.Soetomo Surabaya who performs 10 to 12 hours of fasting with TG less than 400 mg / dL. The sampleconsisted of 41 men and 48 women with an average age of 52 years. The statistical test on each cLDLC gave the Friedewald -1.32% bias value; Anandaraja -3,92%; Puavilai 4.26%, Chen -2.19%; Vujovic-23.65%; de Cordova -0.91% and Dansethakul 4.45%. The correlation coefficient on Friedewald0.9509; Anandaraja 0.9013; Puavilai 0.9576, Chen 0.9585; Vujovic 0.8745; de Cordova 0.9300 andDansethakul 0.9505. The proposed cLDL-C formula Chen et al promises in determining the LDL-Cestimate and the Vujovic formula gives a poor result in this study. Validation methods should be appliedto each of the cLDL formulas if they are to be applied to clinical laboratories.